Cover Image. (7th February 2020) - Bhoopathy, Raghavi; Kunz, Oliver; Juhl, Mattias; Trupke, Thorsten; Hameiri, Ziv
Abstract : The cover image is based on the Applications Outdoor photoluminescence imaging of solar panels by contactless switching: Technical considerations and applications by Raghavi Bhoopathy al., https://doi.org/10.1002/pip.3216 .